ANALISIS STRATEGI PENGEMBANGAN USAHA PELAYANAN JASA ALAT DAN MESIN PERTANIAN (UPJA) DI KABUPATEN BOLAANG MONGONDOW TIMUR - Widjoyo Syuyono Mamonto; Richard E. M. F. Osak; Jolanda Kitsia Juliana Kalangi (AGRI-SOSIOEKONOMI, 2020)
This study aims to examine internal factors and external factors in developing a business in Alsintan Services (UPJA). And the formulation of strategy formulations in growing and developing business businesses in agricultural equipment services or UPJA. The research was conducted from July to August 2020. Located in three districts, namely Kotabunan District, Mooat District and Modayag District, Bolaang Mongondow Timur Regency. Sources of data in this study use primary and secondary data. Data analysis in this study uses the SWOT analysis method based on logic to be able to develop the maximum strength (strength) and opportunity (opportunity), but at the same time can also minimize weaknesses (weakness) and threats (threats). The results showed that the study of internal factors and external factors in the development of agricultural machine tool service business (UPJA), namely internal factors, namely the ability in company managerial and the experience of operators can be called strengths and also company administration in services to farmers and external factors of companies that participate in determining the direction of the development of agricultural equipment service businesses, namely government support, in this case the East Bolaang Mongondow Regency Agriculture Office and the potential for the availability of bank loans which are very supportive for the development of Agricultural Machine Tool Service Business Services (UPJA) as well as guarantee and ease of spare parts Then from the threat factor is the factor that gets attention, namely the low knowledge of farmers and farmers' capital for the use of alsintan. The formulation of the strategy for developing the Agricultural Machine Tool Service Business (UPJA) is an aggressive strategy or in quadrant I where the strategy used is all the strengths to take advantage of existing opportunities, as an alternative strategy to carry out socialization with the support of local governments through related agencies, fostering cooperation with farmers, increasing other agricultural business opportunities owned by UPJA, and increasing the availability of agricultural machinery.